THE IMPACT OF BOARD INDEPENDENCE, PROFITABILITY, LEVERAGE, AND FIRM SIZE ON INCOME SMOOTHING IN CONTROL OF AGENCY CONFLICT - Ekadjaja, Agustin; Andre Chuandra; Margarita Ekadjaja (Jurnal Ekonomi Manajemen Sistem Informasi, 2020)
This research is aimed to earn empirical results about the effect of board independence, profitability, leverage and firm size on income smoothing. The study used purposive sampling as its sampling method on manufacture companies that’s listed on BEI for years 2015-2017. Information for this research was acquired from multiple online sources that store financial reports of companies. This research used Eckel Index to determine if a corporation did an income smoothing on its financial report or not. The results were significant relationships between board independence and income smoothing and between profitability and income smoothing while insignificant relationships were found in between leverage and income smoothing and between firm size and income smoothing. To improve this study there are mulitple ways that has been written in conclusion part.